(untitled) (diségno, 2017)
The relationship between drawing and architecture is one of the historical issues of the art of building. Considered by some historians, critics and architects as a simple tool, it is, however, regarded by other scholars and designers as a much more complex area, to the point that it would not be possible to write a history of architecture while eliminating the results of this graphic exercise. Many works which have remained on the drawing board are, in fact, milestones necessary for describing the significance of a period in the history of architecture which, if it were illustrated only by the buildings that were actually constructed, would not be able to reveal the fabric of the ideas being confronted at the time.